1991
DOI: 10.1159/000293003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Possible Interaction of the Antifungal Triazole SCH 39304 with Oral Contraceptives in Normal Healthy Women

Abstract: The possible interaction of the newly developed triazole antifungal SCH 39304 with low-dose combined oral contraceptives (OCs) was studied in 15 healthy women. Serum levels of ovarian and adrenocortical steroids and sex hormone-binding globulin (SHBG) were analyzed in samples collected during the OC cycles immediately before, during and after the administration of SCH 39304. The drug was given as a single 400-mg oral dose on day 7 in the second cycle. SCH 39304 did not interfere with the ovulatory inhibitory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Most broad-spectrum antibiotics do not affect the contraceptive effectiveness of COCs, patch (345), or ring(346). Studies of antifungal agents have shown no clinically significant pharmacokinetic interactions with COCs(347)(348)(349)(350)(351)(352)(353)(354)(355)(356), or ring(357). Studies of antiparasitic agents have shown no clinically significant pharmacokinetic interactions with COCs(236,(358)(359)(360)(361)(362).…”
mentioning
confidence: 99%
“…Most broad-spectrum antibiotics do not affect the contraceptive effectiveness of COCs, patch (345), or ring(346). Studies of antifungal agents have shown no clinically significant pharmacokinetic interactions with COCs(347)(348)(349)(350)(351)(352)(353)(354)(355)(356), or ring(357). Studies of antiparasitic agents have shown no clinically significant pharmacokinetic interactions with COCs(236,(358)(359)(360)(361)(362).…”
mentioning
confidence: 99%
“…Most broad-spectrum antibiotics do not affect the contraceptive effectiveness of COCs, patch (345), or ring(346). Studies of antifungal agents have shown no clinically significant pharmacokinetic interactions with COCs(347)(348)(349)(350)(351)(352)(353)(354)(355)(356), or ring(357). Studies of antiparasitic agents have shown no clinically significant pharmacokinetic interactions with COCs(236,(358)(359)(360)(361)(362).…”
mentioning
confidence: 99%